Progressive Muscle Relaxation Training During Pregnancy: Effects on Mental State, Delivery and Labour Pain – a Prospective Study - Weschenfelder, Friederike; Bulgay-Mörschel, Mehtap; Lütje, Wolf; Schleußner, Ekkehard (Geburtshilfe und Frauenheilkunde, 2024)
Progressive muscle relaxation is a widely used technique for relaxation, but studies are rare about efficacy on pregnancy and perinatal outcomes. Aim of our study was to determine whether progressive muscle relaxation affects anxiety and depression levels of pregnant women, pregnancy outcomes, labour pain and analgesic requirements.156 pregnant women were enrolled in a prospective non-randomized controlled cohort study. The control group received standard antenatal care and classes only, while the intervention group additionally received progressive muscle relaxation training once a week for six weeks. Anxiety, depression and current strain were measured in a pretest-posttest experimental design using self-report scales at baseline (1st survey), 5 weeks later (2nd survey) and during puerperium (3rd survey). Numeric Rating scales were used for measuring labour pain and satisfaction with analgesic treatment in the 3rd survey.Fifty complete questionnaires from each group were analysed. There were no differences in mental status between the groups at baseline. Progressive muscle relaxation training significantly reduced depression levels. Trait anxiety, reflecting a person’s basic anxiety decreased significantly in both groups during puerperium. No differences in pregnancy outcomes, labour pain and analgesic requirements could be shown within both groups in general. Nonetheless, women attending more than five progressive muscle relaxation courses reported significantly less labour pain within the group and compared to controls.Pregnant women could benefit from progressive muscle relaxation training if used continuously. Relaxation methods should be a substantial part of prenatal care and available for everyone.
Keywords: progressive relaxation; pregnancy; anxiety; depression; labour pain